Effects of wounding and relative humidity on the incidence of Phytophthora root and stem rot in soybean seedlings. (December 2021) - Tada, Terufumi; Tanaka, Chihiro; Katsube-Tanaka, Tomoyuki; Shiraiwa, Tatsuhiko
Abstract: Phytophthora root and stem rot (PRSR) caused by Phytophthora sojae is a major constraint in soybean production. The effects of wounding and relative humidity (RH) on PRSR-induced damage, specifically on the mortality and infection rates in soybean seedlings, which have never been experimentally shown, were investigated. Seedlings were inoculated with P. sojae after being wounded in one of four ways (shallow, moderate, deep, or penetrative incision) or left unwounded. Immediately after inoculation, plants were subjected to five different RH treatments: 3-day wet (100% RH), 1-day wet, ambient (approximately 80% RH), 1-day dry (approximately 60% RH), and 3-day dry treatments. All wounded but uninoculated seedlings survived. The mortality rate ranged from 1 to 99% across all wounding treatments. All unwounded seedlings inoculated with the pathogen survived under all RH treatments. The mortality rates of inoculated seedlings with shallow to deep wounding increased with higher RH. The infection rate followed the same pattern as the mortality rate. Furthermore, the ratio of brown tissues in the cross section of seedlings correlated with wounding depth. These findings demonstrate that the degree of wounding is a crucial determinant of PRSR development, and high RH stimulates disease incidence. Highlights: ・ Soybean seedlings were wounded in various ways and infected with Phytophthora sojae . ・ Mortality rate was 0–1% for unwounded plants. ・ Mortality rate varied from 1 to 99% for wounded plants by wounding depth. ・ High humidity at infection enhanced the mortality of moderately wounded plants.